UMA ÁNALISE EXEGÉTICA DA PORÇÃO DE MIQUEIAS 2,1-5: A SITUAÇÃO SOCIOECONÔMICA EM JUDÁ E SUAS IMPLICAÇÕES NA HERANÇA DOS CAMPONESES NA SEFELÁ JUDAÍTA NO SÉCULO VIII A.C. - Salgado, Samuel de Freitas (2009)
This research seeks to examine trough the exegetic methodology of the passage of Micah 2.1-5 in order to reconstruct the scenario in which emerged the harsh social criticism of the prophet. The text presents in its literary analysis, features of a prophetic speech united and framed within a poetic style. Its structure is divided into two units (denounces and punishments), where each unit has two other subunits (generic and specific). The literary genre harmonizes with a speech of a prophetic judgement generally known as "oracle hoy." The analysis of the historical dimension lies the founding event in 701 B.C. in Jewish Shephelah. An investigative analysis of the accusation contents was guided by a theoretical model of the Tributary Mode of Production observes a conflict between two groups. In this conflict Micah made an accusation to a group of power in Judah that used to plan and execute criminal acts against peasant heritage. The punishment describes the conspiracy and the divine plan against this group of power. Yahweh had planned an identical evil to what they had done, dishonor and deprive of their possessions. The cultural values of honor and shame underlie this oracle. For breaching their duties close to Yahweh and to the people, the criminals would lose all their rights and, above all, the honor before the own community. Based in the theoretical model from the Tributary Mode of production, it was verified in the social situation of Judah in the eighth century, a tension existed between village and city. The communities villages paid tribute to the city, as products and services. The excessive tribute s collection and the flaws in the system of mutual help forced the individuals and families to contract debts, to mortgage their inherited land of their parents and eventually to lose them. The prophet Micah was the spokesman of the protest of the peasant class that decides to react to the abuses practiced by city s elite. For him, Yahweh listens the complaint of those who are being oppressed and intervenes in the history, taking the oppressed side.(AU)